Existence of Customary Land According to the Basic Agrarian Law - Gevan Naufal Wala (CV. Rayyan Dwi Bharata, 2023)
Land tenure by indigenous peoples tends to be ignored. This situation occurs because government policies do not pay attention to developments in land tenure by indigenous peoples. In essence, customary law is law that is recognized for public purposes. Because of this, the state and government should provide protection for the rights of indigenous peoples which are included in the state constitution. This is also stated in Law Number 5 of 1960 concerning Basic Agrarian Regulations. Traditionally owned land or called ulayat land, in essence according to custom is land that cannot be contested and cannot be owned in the form of individuals. However, in these regulations, land can become land rights that can be owned individually without erasing the existence of customary land from customary law communities in Indonesia. The existence of customary law will never retreat or be displaced from the world of politics in building national law, considering that customary law has the ability to adapt and be flexible.